Utilization of Plastic Waste as a Medium for Weaving Crafts: An Expressive Study in Grade VII at SMPN 4 Cikarang Barat - Raihan Nabila Syifa; Gunadi Gunadi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The purpose of this research is to investigate in depth how seventh graders at SMPN 4 Cikarang Barat use plastic trash as a medium for weaving crafts as part of their expressive learning. An ecologically conscious and contextually aware art education is the impetus for this study's foundational work. Students' comprehensive understandings and experiences with recycled craft methods were investigated using a qualitative methodology based on a case study type. Fifteen students and two teachers participated in semi-structured interviews, while visual documentation of students' woven products (carpets, bags, and baskets produced from recycled plastic) and participatory observation during the crafting process completed the data collection. The thematic analysis yielded three primary conclusions: (1) the creative process encourages collaborative and contextual learning, (2) crafts become a means of self-expression that reflect students' identities and personal experiences, and (3) the growth of ecological awareness through meaningful recycling practices. These findings reinforce the theory of social constructivism and eco-literacy, and affirm that recycled crafts are not merely technical skills, but rather media for symbolic expression and the transformation of environmental values. This research contributes to expanding the understanding of crafts as a multidimensional educational medium and provides practical implications for the development of sustainability-based art curricula. In order to provide a more in-depth examination of the symbolic characteristics of crafts or to apply a comparable method in various cultural contexts and educational levels, further research is necessary.